Изменения полномочий и положения Народного консультативного конгресса после внесения поправок в Конституцию Республики Индонезии (Shifting Authority and Position of the People's Consultative Assembly after the Amendment to the Constitution of the Republic of Indonesia) - Shagieva, Rozalina Vasilevna; Nur, Rohim (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
After the amendment to the 1945 Constitution, there was a shift in the authority and position of the People's Consultative Assembly of the Republic of Indonesia. Previously the MPR was the highest state institution, but after that it was only a high institution like other high state institutions. The position of the MPR when compared to the world parliament model, is similar to the Russian Federal Assembly or the Congress in the United States which is a joint institution between the upper house and lower house. But uniquely the MPR is different, it is not only a joint institution, but has the authority with its own duties and functions. This study uses a qualitative method, with a statutory and literature approach. The results of the study stated that there were several shifts in the authority and position of the MPR after the amendment to the 1945 Constitution. Among them were no longer being the highest state institution, only being a joint institution while still having its own duties and functions, not authorized to form the Outlines of State Policy, no longer authorized elect the president and vice president, and rigid authority to dismiss the president and vice president.Keywords: People's Consultative Assembly; Authority; position; The 1945 Constitution. Abstrak:Pasca perubahan Konstitusi UUD 1945 maka terjadi pergeseran kewenangan dan kedudukan Majelis Permusyawaratan Rakyat Republik Indonesia. Sebelumnya MPR menjadi lembaga tertinggi negara namun setelahnya ia hanyalah lembaga tinggi sebagaimana lembaga tinggi negara lainnya. Kedudukan MPR bila dibandingkan dengan model parlemen dunia, mirip dengan Majelis Federal Rusia atau Konggres di Amerika Serika yang menjadi lembaga gabungan antara majelis tinggi dan majelis rendah. Namun uniknya MPR berbeda, ia tidak hanya menjadi lembaga gabungan, tetapi memiliki kewenangan dengan tugas dan fungsi tersendiri. Penelitian ini menggunakan metode kualitatif, dengan pendekatan perundang-undangan dan literature. Hasil penelitian menyatakan bahwa terjadi beberapa pergeseran wewenang dan kedudukan MPR pasca perubahan UUD 1945. Diantaranya adalah tidak lagi menjadi lembaga tertinggi negara, hanya menjadi lembaga gabungan dengan tetap memilik tugas dan fungsi tersendiri, tidak berwenang membentuk Garis-Garis Besar Haluan Negara, tidak lagi berwenang memilih presiden dan wakil presiden, dan kewenangan rigid dalam memberhentikan presiden dan wakil presiden.Kata Kunci: Majelis Permusyawaratan Rakyat; Kewenangan; Kedudukan; Konstitusi UUD 1945. Изменения полномочий и положения Народного консультативного конгресса после внесения поправок в Конституцию Республики Индонезии Аннотация:После внесения поправок в Конституцию 1945 г. произошли изменения в полномочиях и положении Народного консультативного конгресса Республики Индонезии. Предварительно, MPR был верховным государственным учреждением, а потом стал только высшим учреждением, как и другие высшие государственные учреждения. Положение MPR по сравнению с моделью мирового парламента аналогично Федеральному собранию России или Конгрессу США, который является совместным учреждением верхней и нижней палат. Однако MPR уникально отличается тем, что он является не только совместным учреждением, но и имеет полномочия со своими обязанностями и функциями. В этом исследовании используется качественный метод с законодательным и литературным подходами. Результаты исследования показали, что после внесения поправок в Конституцию 1945 г. произошло несколько изменений в полномочиях и положении MPR. Среди них, MPR больше не является верховным государственным учреждением, а является только совместным учреждением, но при этом имеет свои собственные обязанности и функции, не имеет права формировать Общие направления государственной политики, больше не имеет права избирать президента и вице-президента, и не имеет жестких полномочий по увольнению президента и вице-президента.Ключевые слова: Народный консультативный конгресс; Полномочие; Положение; Конституция Республики Индонезии 1945 г.